2022
DOI: 10.1002/cncy.22573
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of extended high‐risk HPV genotyping in risk‐stratifying women with L‐SIL cytology: A retrospective study of 8726 cases

Abstract: BACKGROUND:The value of extended high-risk human papillomavirus (hrHPV) genotyping for cervical cancer screening in women with low-grade squamous intraepithelial lesion (L-SIL) cytology has been recognized, but few studies have investigated this. METHODS: Women with L-SIL Papanicolaou results who underwent human papillomavirus (HPV) genotyping between October 2017 and October 2021 at the Obstetrics and Gynecology Hospital of Fudan University were identified.Their HPV results were correlated with immediate hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…HPV26, a potential hrHPV, had a low prevalence but showed a higher OR for CIN2+ than the majority of traditional hrHPV. One study from our hospital showed that HPV26 was one of the top 5 CIN2+-associated HPV infection types in patients with LSIL cytology [29]. Thus, HPV26 should probably be considered a "high-risk" type.…”
Section: Discussionmentioning
confidence: 96%
“…HPV26, a potential hrHPV, had a low prevalence but showed a higher OR for CIN2+ than the majority of traditional hrHPV. One study from our hospital showed that HPV26 was one of the top 5 CIN2+-associated HPV infection types in patients with LSIL cytology [29]. Thus, HPV26 should probably be considered a "high-risk" type.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been identified in Korean and Danish women at prevalences of 9.3% and 1.6%, respectively 32,47 . The prevalence of HPV82 in multiple studies from China has been low (0.6%–1.2%), but accounts for 10%–30.8% of CIN2 + lesions 24,45,46 …”
Section: Discussionmentioning
confidence: 99%
“…32,47 The prevalence of HPV82 in multiple studies from China has been low (0.6%-1.2%), but accounts for 10%-30.8% of CIN2 + lesions. 24,45,46 Our patient cohort was mostly comprised of unvaccinated women who predominantly underwent cervical biopsy due to abnormal cervical screening test results. Although several HPV vaccines are available in China, they have not yet been officially included in the national vaccination program.…”
Section: Distribution Of Hrhpv Genotypes In Endocervical Glandular Le...mentioning
confidence: 99%
See 1 more Smart Citation
“…HPV is a DNA virus comprising more than 100 genotypes. Thirteen high-risk HPV (hrHPV) types including type 16,18,31,33,35,39,45,51,52,56,58,59, and 68, account for more than 90% of cervical cancers, with HPV16 and HPV18 being the most common oncogenic genotypes. Clinically, hrHPV status is usually determined by HPV pooled assays with limited genotyping (HPV16 and HPV18) (2).…”
Section: Introductionmentioning
confidence: 99%